2017
DOI: 10.3961/jpmph.17.098
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease–related Health Beliefs and Lifestyle Issues Among Karen Refugees Resettled in the United States From the Thai-Myanmar (Burma) Border

Abstract: ObjectivesRefugees resettled in the US may be at risk for cardiovascular disease (CVD). However, little is known about CVD-related issues among Karen refugees who have migrated to the US from the Thai-Myanmar border. The purpose of this study was to examine CVD-related health beliefs and lifestyle issues among Karen refugees resettled in the US.MethodsKaren refugees resettled in the US from the Thai-Myanmar border (n=195) participated in a survey study on health beliefs related to CVD, salt intake, physical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…These assessments can build a more comprehensive health profile of resettled refugees to inform public health practice and allow for targeted screening and clinical interventions beyond the initial resettlement period. Prevalence of EBLL > 10 mcg/dL was 7% [41]…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These assessments can build a more comprehensive health profile of resettled refugees to inform public health practice and allow for targeted screening and clinical interventions beyond the initial resettlement period. Prevalence of EBLL > 10 mcg/dL was 7% [41]…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, several studies noted that refugee adults have higher prevalence and/or odds of chronic diseases compared with other populations. Several factors may influence risk or progression of chronic diseases among refugee populations including individual-level factors such as reduced consumption of healthy foods (e.g., reduced fruit and vegetable intake) [29,[41][42][43], reduced physical activity [29,41,42,44,45], limited health literacy [46], varied perceptions and beliefs on health and health care [47][48][49], limited English proficiency and subsequent challenges in communication [49][50][51], and reduced access to health care [7,48,50,51]. While there may be multiple reasons for decreased healthy eating among resettled refugee populations in the US (relative to the US general population), acculturation has been identified as an important contributor.…”
Section: Discussionmentioning
confidence: 99%
“…Video (Piwowarczyk et al , 2013) and community based participatory research in a faith community (Shirazi et al , 2015) have both been used to target refugee and immigrant newcomers to the USA by addressing health beliefs. Public health interventions have been recommended to address high-salt diet, physical inactivity and smoking habits among refugees resettled in the USA (Kamimura et al , 2017). When examining preventive care perceptions among Eritrean refugees in the USA, the thirst for information was an overarching theme underscoring the need to create health promotion programs that focus on both community engagement as information dissemination (Worabo, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Four studies examined SEAR's health behaviors. According to Kamimura et al (2017), Karen refugees from the Thai-Myanmar border who had been in the US about 6 years had high rates of smoking (22% among women, 16.3% among men). Burmese refugees within 31 days of their resettlement in the US had even higher rates of smoking (31%; Weinmann et al, 2021).…”
Section: Risk Factors For Poor Mental and Physical Healthmentioning
confidence: 99%
“…In addition, high costs or lack of insurance were also important barriers to healthcare access (Stephens et al, 2011). Kamimura et al (2017) reported that 31% of the Karen refugees did not have medical insurance and 44% did not have dental insurance, which reduced their ability to access to care.…”
Section: Barriers To Healthcare Accessmentioning
confidence: 99%